2014
DOI: 10.1007/s13193-014-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Thyroid Lesions and its Correlation with Histopathology in a Series of 248 Patients

Abstract: Thyroid swellings are a significant clinical problem in the general population but majority of them are nonneoplastic and do not require surgery. The initial screening procedures include ultrasonography, fine needle aspiration cytology (FNAC) and radionucleotide scan. An initial screening test which will diagnose thyroid lesions accurately will help to avoid surgery in nonneoplastic conditions. The aim of the present study is to correlate the cytology findings with final histopathology. Two hundred and forty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The overall accuracy of cyto-cell block for detection of neoplasm was 94%, with a sensibility and specificity of 100% and 90%, respectively. Thyroid nodules are a significant clinical problem in the general population but the majority of them are benign and do not require surgery (15). Indeed, the prevalence of thyroid carcinomas is approximately 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy of cyto-cell block for detection of neoplasm was 94%, with a sensibility and specificity of 100% and 90%, respectively. Thyroid nodules are a significant clinical problem in the general population but the majority of them are benign and do not require surgery (15). Indeed, the prevalence of thyroid carcinomas is approximately 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Though only 10-15% of the cysts are neoplastic, FNA from solid area would reduce the misinterpretation and false negativity in cystic neoplasms. [16,17,18] For malignancies, FNAC showed sensitivity of 40%, specificity of 97.1%, positive predictive value of 66.6%, negative predictive value 91.9% and efficacy of 90%. Previous studies on FNAC of solitary thyroid nodule have showed sensitivity and specificity of 68.1% and 100%(Agarwal SK et al), 75% and 100% (Bapat et [6,8,[19][20][21][22][23][24][25][26] Akerman et al have quoted that the reasons for low sensitivity could be that tumor being missed at aspiration, misinterpretation of cytologic findings, cellular atypia, indeterminate diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Among these, the FNAC is considered the most accurate diagnostic modality [3]. The Bethesda system of thyroid cytologyreporting makes the reports clinically relevant and helps the clinicians to take appropriate therapeutic interventions [4]. FNAC is a well-established outpatient procedure used in primary diagnosis of thyroid swellings and assumed dominant role in the management mainly to rule out need of surgery [5,6].…”
Section: Introductionmentioning
confidence: 99%